Structural behaviour of precast concrete wall frame connections under shear load - Rossley, Nabila (2014)
Connection design is one of the most important considerations for the successful construction of precast reinforced concrete structures. There are two types of connections known as loop steel bar is used as vertical connection, to connect wall to wall and exterior-interior wall and the horizontal connection refers to grouted splice sleeve connection which is used to connect top and bottom wall and tested on wallslab-wall specimens. 12 specimens were prepared which consisted of three wall to wall specimens, three exterior-interior wall specimens and six exterior wall-slab specimens. To study the vertical connection, the wall to wall connection specimens (WWC) were subjected to in plane shear load, whilst the exterior-interior wall connection specimens (EIWC) were subjected to out of plane shear load. On the other hand, the horizontal connection is by the wall-slab-wall connection specimens (WSW) when subjected to lateral load. The aim of this research is to determine the behaviour of these two connections. WWC specimens have shown that the loop connection that is used to connect adjacent walls was considered as brittle. The connection tends to collapse abruptly when it was overloaded. Although it is brittle, the test results have proven that the loop connection is able to give crack lines at the interface before failure occurred. The maximum shear stress attained for loop steel bar connection for these specimens were higher than the maximum design shear stress allowed. Hence for this size of specimens, the size of the loop bar connection should be reduced. The strut and tie model of the loop joint was used to model flow of forces in the vertical connection through EIWC specimens. The crack showed a zigzag pattern and it was developed as the force from one precast element to the other was transmitted by inclined compressive struts between overlapping loop bar. The average ductility factor of EIWC specimens was 2.43, which was below the range of requirement for seismic ductility normally between 3 and 6. Therefore, this connection could be categorise as a brittle connection. The horizontal connection known as grouted splice sleeve connection was used to connect WSW specimens. The specimens were subjected to out plane loading to represent possibility of wind load on the wall. The maximum moment obtained is larger than the required moment for 8 stories building. From the lab test, it shows that this connection only able to transfer compression between the upper and lower walls whilst the connection bar was only suitable for positioning.